2004
DOI: 10.1364/opex.12.006270
|View full text |Cite
|
Sign up to set email alerts
|

Small core rib waveguides with embedded gratings in As2Se3 glass

Abstract: Low-loss shallow-rib waveguides were fabricated using As2Se3 chalcogenide glass and polyamide-imide polymer. Waveguides were patterned directly in the As2Se3 layer by photodarkening followed by selective wet etching. Theory predicted a modal effective area of 3.5-4 microm2, and this was supported by near-field modal measurements. The Fabry-Perot technique was used to estimate propagation losses as low as ~0.25 dB/cm. First-order Bragg gratings near 1550 nm were holographically patterned in some waveguides. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…21 To date, in reports of holographically written Bragg gratings in ChG-based fibers and waveguides, Mach-Zehnder interferometers have been employed, 15,16,[22][23][24] which are par- ticularly sensitive to environmental disturbances (mechanical vibrations, thermal gradients, and air currents). This sensitivity affects the stability of the interference pattern over time and hence the quality of the Bragg grating-especially during long write times.…”
Section: Waveguide Structure and Writing Setupmentioning
confidence: 99%
“…21 To date, in reports of holographically written Bragg gratings in ChG-based fibers and waveguides, Mach-Zehnder interferometers have been employed, 15,16,[22][23][24] which are par- ticularly sensitive to environmental disturbances (mechanical vibrations, thermal gradients, and air currents). This sensitivity affects the stability of the interference pattern over time and hence the quality of the Bragg grating-especially during long write times.…”
Section: Waveguide Structure and Writing Setupmentioning
confidence: 99%
“…8 Furthermore Ponnampalam et al 9 reported the production of rib waveguides by selective chemical etching of photodarkened As 2 Se 3 glass and obtained losses also down to 0.25 dB/ cm. These values are sufficiently low to allow integrated devices containing waveguides several tens of centimeters long to be fabricated.…”
mentioning
confidence: 99%
“…TPA and FCA losses are negligible in chalcogenide glasses, benefited from their large optical bandgap and low carrier mobility 2 . Furthermore, successful fabrications of µm-size chalcogenide rib waveguide using standard complimentary metal-on-silicon (CMOS) have been demonstrated recently, making them an ideal choice for on-chip laser source 3,4 . As 2 Se 3 looks particularly appealing for waveguide Raman laser with its highest reported Raman gain 6 .…”
Section: Introductionmentioning
confidence: 99%